Genetic diversity of clones of acerola assessed by ISSR molecular markers - Lima, Eveline Nogueira; de Araujo, Maria Emilia Bezerra; Magalhães Bertini, Candida Hermínia Campos de; Moura, Carlos Farley Herbster; Crestani, Maraisa (Comunicata Scientiae, 2015)
The Indian cherry (Malpighia emarginata) is a tropical fruit originated from American continent. In Brazilian orchards, there was high variability among cultivated genotypes. On the order hand, high variability allows the identification of superior genotypes for cropping industry. This study aimed to evaluate the genetic variability among 56 genotypes using ISSR (Inter Simple Sequence Repeats) primers. Leaf samples were collected in Pacajus-CE and taken to the laboratory of Molecular Biology postharvest, in Fortaleza. Altogether, 20 primers were used which yielded 148 polymorphic bands (79.57%), enabling the differentiation within the population study. As a result, this information may be used in future studies on breeding programs, such as choosing best combinations for parental crossings.